Prognostic Significance of Left Ventricular Mass Index and Renal Function Decline Rate in Chronic Kidney Disease G3 and G4 - Huang, Jiun-Chi (Sci Rep, 2017)
The effect of left ventricular mass index (LVMI) and estimated glomerular filtration rate (eGFR) decline rate on outcome prediction in patients with chronic kidney disease (CKD) remains unclear. We included 306 CKD G3 and G4 patients with LVMI assessed through echocardiography. Rapid decline in renal function was defined as the eGFR slope <−3 mL/min/1.73 m(2)/year. Patients were stratified into four groups using sex-specific median values of LVMI and rapid eGFR decline. The composite outcome was progression to maintenance dialysis or death. 32 patients had the composite outcome during a median follow-up of 2.7 years. In multivariate Cox analysis, compared with patients with non-rapid eGFR decline and lower LVMI, those with non-rapid eGFR decline and higher LVMI (hazard ratio [HR]: 5.908, 95% confidence interval [CI] = 1.304–26.780), rapid eGFR decline and lower LVMI (HR: 12.737, 95% CI = 2.297–70.636), and rapid eGFR decline and higher LVMI (HR: 15.249, 95% CI = 3.365–69.097) had an increased risk of progression to adverse outcomes. LVMI and eGFR decline synergistically effect the prognostic implications in CKD G3 and G4 patients.